2017
DOI: 10.17323/1998-0663.2017.3.20.29
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the influence of foreign investments on food security based on panel cointegration models

Abstract: АbstractThe paper studies the problems of food security as the basis for the stability of the country's economic development. Despite the economic growth of most countries in the world, the problems of hunger continue to be acute in developing countries. This undermines the food security of these countries and can pose a threat to world peace as a whole. Numerous studies show that foreign investment plays an important role in the creation of food security, but this eff ect is ambiguous. The most common methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Kopnova and Rodionova [ 20 ], studied the determinants of food security using time series data, found population growth and foreign aid as the dominant determinants, studies that utilised household data in the different rural and urban context identified sociodemographic and economic status among other factors as the major determinants of food security or insecurity. Nonetheless, there is a growing body of literature investigating the nexus between COVID‐19 and food security amongst other indicators of sustainable development.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Kopnova and Rodionova [ 20 ], studied the determinants of food security using time series data, found population growth and foreign aid as the dominant determinants, studies that utilised household data in the different rural and urban context identified sociodemographic and economic status among other factors as the major determinants of food security or insecurity. Nonetheless, there is a growing body of literature investigating the nexus between COVID‐19 and food security amongst other indicators of sustainable development.…”
Section: Empirical Reviewmentioning
confidence: 99%